Altmetrics in Plastic Surgery Journals: Does It Correlate With Citation Count?. (7th June 2020) - Asaad, Malke; Howell, Skyler M; Rajesh, Aashish; Meaike, Jesse; Tran, Nho V
Abstract: Background: Altmetrics (alternative metrics) have become one of the most commonly utilized metrics to track the impact of research articles across electronic and social media platforms. Objectives: The goal of this study was to identify whether the Altmetric Attention Score (AAS) is a good proxy for citation counts and whether it can be employed as an accurate measure to complement the current gold standard. Methods: The authors conducted a citation analysis of all articles published in 6 plastic surgery journals during the 2016 calendar year. Citation counts and AAS were abstracted and analyzed. Results: A total of 1420 articles were identified. The mean AAS was 11 and the median AAS was 1. The journal with the highest mean AAS was Aesthetic Surgery Journal (31), followed by Plastic and Reconstructive Surgery (19). A weak positive correlation was identified (r = 0.33, P  < .0001) between AAS and citations. Articles in the top 1% in terms of citation counts showed strong positive correlation between AAS and citation counts (r = 0.64, P  = .01). On the contrary, articles in the top 1% of AAS had no significant correlation with citation counts (r = −0.31, P  = .29). Conclusions: Overall correlation between citations and AAS was weak, and therefor AAS may not be an accurate early predictor of future citations. The 2 metrics seem to measure different aspects of the impact of scholarly work and should be utilized in tandem for determining the reach of a scientific article.